2010
DOI: 10.1021/op900336a
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic and Mass Transfer Model for Glycerol Hydrogenolysis in a Trickle-Bed Reactor

Abstract: A detailed model of glycerol hydrogenolysis in a trickle-bed reactor is presented that includes a mechanistically based kinetic rate expression, energy transport, mass transport across the gas-liquid and liquid-solid interfaces, intraparticle catalyst mass transfer, and partial wetting of the bed. Optimal kinetic parameters for the glycerol hydrogenolysis rate expression were determined via nonlinear regression analysis on the basis of experiments conducted in a laboratory-scale trickle-bed reactor over a broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
2
16
0
3
Order By: Relevance
“…Besides, glycerol showed an endothermic adsorption on Cu surface. A simplified model describing the adsorption of glycerol, glyceraldehyde and acetol on the same site was proposed by Xi and co‐workers . With negligible adsorption of OH − as the promoter and 1,2‐PDO, this model fitted the experimental data very well in the range of 180–200 °C.…”
Section: Figurementioning
confidence: 99%
“…Besides, glycerol showed an endothermic adsorption on Cu surface. A simplified model describing the adsorption of glycerol, glyceraldehyde and acetol on the same site was proposed by Xi and co‐workers . With negligible adsorption of OH − as the promoter and 1,2‐PDO, this model fitted the experimental data very well in the range of 180–200 °C.…”
Section: Figurementioning
confidence: 99%
“…A catalyst composed of Co, Pd and Re supported on activated carbon was used for the kinetic study reported by Xi et al employing a trickle‐bed reactor at a temperature range of 453–475 K and hydrogen pressures 3.3–13.3 MPa . The main reaction steps included (1) dehydrogenation of glycerol to adsorbed glyceraldehyde species, (2) rearrangement and dehydration to a second adsorbed intermediate analogous to pyruvaldehyde (see Figure ), and (3) hydrogenation of the latter to form 1,2‐propanediol.…”
Section: Reaction Kinetic Analysismentioning
confidence: 99%
“…The parity plot showed good agreement between the experimental and predicted data especially at the lower concentration range. The activation energy for glycerol conversion to 1,2-propanediol found to be 54.2 kJ/mol ( 76 The main reaction steps included (1) dehydrogenation of glycerol to adsorbed glyceraldehyde species, (2) rearrangement and dehydration to a second adsorbed intermediate analogous to pyruvaldehyde (see Figure 8), and (3) hydrogenation of the latter to form 1,2-propanediol. The final rate expression (Table 2, entry 3) was simplified and included information about glycerol, hydroxide promoter, and hydrogen.…”
Section: Reaction Kinetic Analysismentioning
confidence: 99%
“…Although several computational studies using density functional theory (DFT) have provided insights into possible activation modes of the C‐C, C‐H, and O‐H bonds of polyols (such as glycerol and EG) on selected metal catalysts, there is a lack of reliable experimental investigations into the intrinsic kinetics of aqueous phase conversion of polyols. Further, while the kinetics of catalytic polyol hydrogenolysis in aqueous medium has been studied in the presence of externally added hydrogen, no such studies exist for tandem catalysis without adding hydrogen from external sources.…”
Section: Introductionmentioning
confidence: 99%